2005
DOI: 10.1089/end.2005.19.360
|View full text |Cite
|
Sign up to set email alerts
|

Initial Impact of a Dedicated Postgraduate Laparoscopic Mini-Residency on Clinical Practice Patterns

Abstract: A 5-day dedicated postgraduate M-R in laparoscopy appears to be helpful for urologists wishing to incorporate this surgical approach into their practices. The "take rate" among participants is initially at the 40% level, similar to what has been previously reported after a 1 to 2-day hands-on didactic laparoscopy course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 3 publications
4
12
0
Order By: Relevance
“…One of the possible reasons robotic surgery has gained such widespread popularity is that the skill set required is mastered more rapidly than the skill set needed for laparoscopic radical prostatectomy. 1,2 The skills required for robotic surgery are different from those needed for purely laparoscopic surgery. Robotic surgical movements are intuitive, whereas purely laparoscopic movements are counterintuitive and rely on the fulcrum effect at the body wall.…”
Section: Introductionmentioning
confidence: 99%
“…One of the possible reasons robotic surgery has gained such widespread popularity is that the skill set required is mastered more rapidly than the skill set needed for laparoscopic radical prostatectomy. 1,2 The skills required for robotic surgery are different from those needed for purely laparoscopic surgery. Robotic surgical movements are intuitive, whereas purely laparoscopic movements are counterintuitive and rely on the fulcrum effect at the body wall.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Assessments of 1-2-day hands-on didactic courses and 5-day dedicated postgraduate "miniresidencies" have found that only approximately 40% of laparoscopy-naïve urologic surgeons will continue to perform laparoscopic nephrectomy 6 month later, and 58% describe this training as insufficient. 6,7 Additional mentoring by a laparoscopic surgeon during laparoscopic cases at the trainee's hospital allowed for 93% to continue performing laparoscopic procedures at 6 months; however, only 72% described their training as sufficient. 6 Whereas it has been established that a HALN expert surgeon may quickly and efficiently transfer this skill to a new medical center and effectively train residents and fellows, 8 there remains a paucity of data regarding the minimum amount of HALN training a midcareer laparoscopy-naïve urologist at a urologic laparoscopy-naïve academic medical center should receive in order to be able to return and immediately initiate HALN resident training, particularly at a lower volume center.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Whereas past investigation into the long-term impact of 2-to 3-day seminars showed decreased use of laparoscopy 5 years after postgraduate training, 5 recent study into weeklong ''mini''-robotic fellowships appear to have a positive impact on participants' minimally invasive practices on 3-year follow-up. 6 This type of training focuses less on didactic material and instead on providing multiple hands-on experiences, ranging from use of models and cadavers to observing and performing procedures on live patients.…”
Section: Discussionmentioning
confidence: 99%